EFEKTIFITAS MODEL AAPTASI ROY DALAM MANAGEMEN KASUS DEMAM NEUTROPENIA PADA ANAK DI RUMAH SAKIT CIPTO MANGUNKUSUMO - Rosa Melati, Allenidekania, Happy Hayati (Institut Kesehatan Hermina, 2020)
Neutropenic febrile is a complication effect of post chemotherapy treatment. This final paper aimed to describe the application of Roy’s Adaptation Model in caring for children with cancer experiencing neutropenic febrile and to describe the achievement of pediatric nurse specialist student’s competencies in clinical practice. During the residency programme, role as caregiver, advocate, educator, collaborator, researcher, and innovator was conducted based on ethic and legal in nursing issues. Roy’s Adaptation Model was implemented on 5 pediatric clients. Nursing process was conducated by behavior and stimuli assessment, nursing diagnosis, nursing outcome, intervention, and evaluation. The children with neutropenia febrile experienced ANC value more than 1000m3 after the care. Roy’s Adaptation Model can be applied in caring for children with cancer in order to improve children’s quality of life.